Fresh Evidence on Technology Leadership and Technology Transformation at Schools in Five Different Continents: Moderating Role of Supply Chain - Shinta Setia; Dian Ekowati (International Journal of Supply Chain Management, 2020)
This paper aims to summarize the knowledge and understanding of technology leadership in educational context, that is still scarce, and gather the empirical evidence on organizational change due to technology transformation at schools in five continents. Further aimed where information sharing wide supply chain management significantly and positively inserts moderating effects among the relationship between simplified organizational structure (SOS), collective decision making (CDM), adequate knowledge and skills (AKS), and organizational change (OC). The research revealed that simplified organizational structure, collective decision making and adequate knowledge and skills have positive association with organzational change, and supply chain positively moderate among the link between AKS and OC. The result also contribute to (1) a considerable variability of terms and definition of technology leadership in the era of industrial revolution 4.0 and (2) theoritical review on managerial practice for successsful technology transformation. From the study, leaders, teachers, and staffs in higher education and all parties involved in the world of education today are able to recognize the importance of adapting to rapid changes, which occur exponentially in the world of education as a result of technology development.